The Changing Patterns of Policy Making in Japan. Local Policy Initiative of Okinawa Prefecture in the 1990s. - Bochorodycz, Beata (My University, 2010)
The research analyzes central-local relations of government in Japan focusing on Okinawa prefecture, and in particular on the process of formulation and negotiation of the Program for Autonomic Modernization of Okinawa (Kokusai toshi keisei kōsō) in the 1990s. It was the most comprehensive regional development plan that had ever been proposed by a local government in Japan. The detailed conclusions identify factors that enabled formulation of projects on the local and national levels, their consecutive setting on the central government agenda, and also those factors and assimilation methods, which shaped the final outcome of the local initiatives on the national level. The main hypothesis of the thesis is that the process of globalization and regional integration in East Asia on one had, and on the other, the activities of local and other political actors aiming at acceleration of decentralization and liberalization of the economy – have had far reaching consequences for the centralized system of the regional development planning in Japan. Key words: local autonomy in Japan, regional planning in Japan, Okinawa, local and national decision making in Japan, local and national policy making in Japan.
Zmieniające się modele polityki w Japonii. Lokalne inicjatywy polityczne w Prefekturze Okinawy w latach 90. XX wieku
Keywords: Regional planning in Japan; Okinawa; Local autonomy in Japan; Local and national decision; Making in Japan; Local and national policy making in Japan